(3Yjhf GdJhGQjNs - (3eMeO Hf TGcQ Hf CMeO Hf YHO GdQMef GdcJHj GdOGQGfqj GdOeTbqj, UdGM GdOjf , J (B764 (3g` s; (3KGHJ Hf CHj KGHJ SYjO Gdchaj , CHh eMeO,J (B250 (3g` s ((3MSf Ydi YHjO GdeQOGOi GdebOSi GdMfHdi s)
(3BNQgG (B:s
(3Edi SfI (B11(3g` s
(3CLRGA eJaQbI fSN eJYOOIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B97 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B100 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B248s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B48 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN P (B- (3bSe (B1 - (3U (B189 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1185s
Keywords: (3GdJGQjNs